2015
DOI: 10.1038/srep15046
|View full text |Cite
|
Sign up to set email alerts
|

Maternal intraguild predation risk affects offspring anti-predator behavior and learning in mites

Abstract: Predation risk is a strong selective force shaping prey morphology, life history and behavior. Anti-predator behaviors may be innate, learned or both but little is known about the transgenerational behavioral effects of maternally experienced predation risk. We examined intraguild predation (IGP) risk-induced maternal effects on offspring anti-predator behavior, including learning, in the predatory mite Phytoseiulus persimilis. We exposed predatory mite mothers during egg production to presence or absence of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
0
21
0
Order By: Relevance
“…This mechanism for transgenerational phenotypic plasticity, or maternal effect, is defined as the ability of a female to alter its offspring's phenotype, allowing it to survive in a specific environment (Bernardo 1996;Mousseau and Fox 1998;Fox et al 1999;Freinschlag and Schausberger 2016). In phytoseiid mites, maternal strategies promoting offspring survival have been associated with food deprivation, risk of intraguild predation, and risk of sibling cannibalism (Toyoshima and Amano 1998;Schausberger and Hoffmann 2008;Schausberger 2011, 2015;Seiter and Schausberger 2015). To our knowledge, only one published study has reported a maternal effect associated with relative humidity in mites: in larvae of the American dog tick Dermacentor variabilis (Say) (Acari: Ixodidae), the ability to absorb water vapor from the air is under maternal control (Yoder et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…This mechanism for transgenerational phenotypic plasticity, or maternal effect, is defined as the ability of a female to alter its offspring's phenotype, allowing it to survive in a specific environment (Bernardo 1996;Mousseau and Fox 1998;Fox et al 1999;Freinschlag and Schausberger 2016). In phytoseiid mites, maternal strategies promoting offspring survival have been associated with food deprivation, risk of intraguild predation, and risk of sibling cannibalism (Toyoshima and Amano 1998;Schausberger and Hoffmann 2008;Schausberger 2011, 2015;Seiter and Schausberger 2015). To our knowledge, only one published study has reported a maternal effect associated with relative humidity in mites: in larvae of the American dog tick Dermacentor variabilis (Say) (Acari: Ixodidae), the ability to absorb water vapor from the air is under maternal control (Yoder et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Learning and memory are thought to be hereditarily transmitted from parents to their filials. In addition to the transmissions of parent's cognitive behaviors directly to their filials, such as specific odor-induced fear memory [ 3 ] and anti-predation behavior [ 4 ], the ability of learning and memory may be transmitted from parents to their filials. Genetics and epigenetic regulation are thought to be molecular bases for the transgenerational inheritance of learning ability and memory to specific events [ 9 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are two forms of transgenerational intelligence, the transmission of parent's cognitions and behaviors directly to their filials, such as specific odor-induced fear memory [ 3 ] and anti-predation behavior [ 4 ], as well as the transmission in the ability of learning and memory to their filials [ 5 8 ]. The transmission of specific memory from parents to their filials cannot rule out the maternal effects on filials, such as social learning [ 49 , 50 ] after filials are born.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These hypotheses suggest that during development, individuals are physiologically (and thus behaviourally) "tuned" to respond to salient environmental cues in a way that maximises fitness in later life (19,83,107,108).The adaptive significance of this programming may only become evident under certain contexts in later life, such as when later environments match this experienced in development (109,110). For example, in mites pre-natal exposure to the risk of predation produces offspring that are less active when living in high predation areas (111). This result provides evidence for a possible adaptive response, in that it allows parents to communicate cues about the likely state of the post-natal environment (i.e.…”
Section: Long-term Effectsmentioning
confidence: 99%